2007
DOI: 10.1080/03601230701465593
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and half-life of the herbicide tebuthiuron on a recharge area of Guarany aquifer in sugarcane fields in Brazil

Abstract: This study was undertaken to evaluate the degradation and mobility of the herbicide tebuthiuron (N-[5-(1,1-dimethylethyl)-1,3,4-thiadiazol-2-yl]-N,N'-dimethylurea) in soil under field conditions, and its potential for leaching and groundwater contamination. A watershed, Espraiado, located over a recharge area in Brazil, was chosen for soil and water studies. At Espraiado, water samples were collected from seven wells at intervals of three months from March 2004 to June 2006 and analyzed for tebuthiuron. Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
2
15
0
4
Order By: Relevance
“…Os resultados ainda estão de acordo com aqueles observados por Boeira & Dornelas de Souza (2005), em que o movimento desse herbicida não ultrapassou 20 e 10 cm de profundidade, respectivamente, em solos de textura média e argilosa. Os resultados também confirmam aqueles verificados por Cerdeira et al (2006), que coletaram amostras de solo (textura média e argilosa) em diferentes profundidades e não encontraram resíduos de tebuthiuron abaixo de 40 cm.…”
Section: Resultsunclassified
“…Os resultados ainda estão de acordo com aqueles observados por Boeira & Dornelas de Souza (2005), em que o movimento desse herbicida não ultrapassou 20 e 10 cm de profundidade, respectivamente, em solos de textura média e argilosa. Os resultados também confirmam aqueles verificados por Cerdeira et al (2006), que coletaram amostras de solo (textura média e argilosa) em diferentes profundidades e não encontraram resíduos de tebuthiuron abaixo de 40 cm.…”
Section: Resultsunclassified
“…Standards of diuron (98.7% pure) and hexazinone (98.5% pure) were donated by DUPONT and tebuthiuron (97.7% pure) from DowAgroSciences. The extraction was conducted as described previously (Matallo et al, 2003(Matallo et al, , 2005Negrisoli et al, 2005;Cerdeira et al, 2007). The following validation parameters were obtained: limit of quantification (LQ) 0.02 mg kg − 1 and limit of detection (LD) of method 0.01 mg kg − 1 ; linearity from 0.050 to 5.00 mg L − 1 (r 2 N 0.999) and recoveries from 90 to 103%.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…They concluded that the more contact time of the herbicide with the straw, the less its transposition to the soil, regardless of the simulated rain quantity, reducing by about 30% the total leached product when this remained exposed for 28 days after application. The active principle of this herbicide (tebuthiuron) presents long half-life, about a year in soils with high carbon content and little rain (Chang and Strizke, 1977;Helling, 2005;Gomes et al, 2006); it may have its half-life reduced up to 20 days under specific soil conditions (moisture, organic matter concentration, microbial community) and climate (temperature, radiation) (Cerdeira et al, 2007). In this study, tebuthiuron was not effective in controlling after 45 days without rain, indicating that the product may have been volatilized and/or photodegraded during this period.…”
Section: Resultsmentioning
confidence: 99%